Plasmaspheric Hiss: Coherent and Intense - Tsurutani, Bruce T.; Park, Sang A.; Falkowski, Barbara J.; Lakhina, Gurbax S.; Pickett, Jolene S.; Bortnik, Jacob; Hospodarsk, George; Santolik, Ondrej; Parrot, Michel; Henri, Pierre; Hajra, Rajkumar (My University, 2018)
Intense ~300-Hz to 1.0-kHz plasmaspheric hiss was studied using Polar plasma wave data. It is found that the waves are coherent in all local time sectors with the wave coherency occurring in approximately three- to five-wave cycle packets. The plasmaspheric hiss in the dawn and local noon time sector are found to be substorm (AE*) and storm (SYM-H*) dependent. The local noon sector is also solar wind pressure dependent. It is suggested that coherent chorus monochromatic subelements enter the plasmasphere (as previously suggested by ray tracing models) to explain these plasmaspheric hiss features. The presence of intense, coherent plasmaspheric hiss in the local dusk and local midnight time sectors is surprising and more difficult to explain. For the dusk sector waves, either local in situ plasmaspheric wave generation or propagation from the dayside plasmasphere is possible. There is little evidence to support substorm generation of the midnight sector plasmaspheric hiss found in this study. One possible explanation is propagation from the local noon sector. The combination of high wave intensity and coherency at all local times strengthens the suggestion that the electron slot is formed during substorm intervals instead of during geomagnetic quiet (by incoherent waves). Plasmaspheric hiss is found to propagate at all angles relative to the ambient magnetic field, Î¸kB. Circular, elliptical, and linear polarized plasmaspheric hiss have been detected. No obvious, strong relationship between the wave polarization and Î¸kB was found. This information of hiss properties should be useful in modeling wave-particle interactions within the plasmasphere.
Keywords: Plasma; Plasmasphere